2022
DOI: 10.1007/s10681-022-02980-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, and biochemical responses of onion (Allium cepa L.) breeding lines to single and combined salt and drought stresses

Abstract: Abiotic stresses deteriorate plant growth resulting in devastating yield losses. Salt stress solely cause ionic toxicity and disturbed homeostasis, whereas combined salt and drought stress has more pronounced effects on plants. Here we performed a pot experiment using 32 Turkish onion breeding lines and commercial cultivars for screening against salt, drought and combined salt and drought stress treatments initiated at the bulbi cation stage under greenhouse conditions. Physiological characteristics, such as g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In Colombia, short-day onion varieties have demonstrated excellent adaptation in regions with warm to moderately cool thermal conditions, ranging from 800 to 2500 m.a.s.l. and temperatures between 16 • C and 27 • C. The formation of bulbs is significantly favored in cultivation areas characterized by high luminosity, high daytime temperatures (25-27 • C), cool nighttime temperatures (16)(17)(18)(19) • C), and relatively low humidity during both day and night (60-70%) [12]. Commonly cultivated onion varieties in Colombia include Yellow Granex, Superex F1, Nirvana F1, Granex Carnaval, Yellow Granex Eden, Texas Early Yellow Gran 502, Red Creole, Colina F1, Híbrido Rojo F1, Rosada Milenio F1, Dulcinea F1, Sierra F1, Roja Eureka F1, and Francisca F1 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Colombia, short-day onion varieties have demonstrated excellent adaptation in regions with warm to moderately cool thermal conditions, ranging from 800 to 2500 m.a.s.l. and temperatures between 16 • C and 27 • C. The formation of bulbs is significantly favored in cultivation areas characterized by high luminosity, high daytime temperatures (25-27 • C), cool nighttime temperatures (16)(17)(18)(19) • C), and relatively low humidity during both day and night (60-70%) [12]. Commonly cultivated onion varieties in Colombia include Yellow Granex, Superex F1, Nirvana F1, Granex Carnaval, Yellow Granex Eden, Texas Early Yellow Gran 502, Red Creole, Colina F1, Híbrido Rojo F1, Rosada Milenio F1, Dulcinea F1, Sierra F1, Roja Eureka F1, and Francisca F1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bulb onion is a shallow-rooted crop; its root penetration is around 0.18 m, so it cannot uptake moisture from deep soils [17]. The root systems of onion plants make them susceptible to fluctuations in soil moisture, leading to decreased yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, a decrease in soil moisture leads to a reduction in onion plant height in the field [ 18 ]. Onion field and greenhouse experiments have shown that 20–45 days of drought negatively affects morphological parameters such as leaf number, length, width, and area, with a high rate of leaf senescence [ 1 , 83 , 84 ]. This proves that leaf senescence is a typical symptom during drought, which increases with stress severity in onions [ 85 ].…”
Section: Effects Of Drought On Onionsmentioning
confidence: 99%
“…Photosynthetic pigments such as chlorophyll a, chlorophyll b, and carotenoids decreased in leaves when drought stress of 10–20 days was imposed on onion seedlings transplanted in pots and greenhouses [ 83 , 92 , 93 ]. This reduction in assimilative pigment levels during the growth phase causes a decrease in the photosynthetic activity, resulting in low organic matter synthesis in onion plants [ 84 ]. Several other works have demonstrated the effect of drought on chlorophyll in onion plants [ 91 , 94 ].…”
Section: Effects Of Drought On Onionsmentioning
confidence: 99%
“…Generally, drought coincides with higher air temperature that enhances evapotranspiration resulting in closure of stomata, reduction in photosynthetic rate and damage to photosynthetic pigments (Giordano et al 2021). Currently, several studies have been reported to reveal the effect of combined stresses to adapt vegetable crops to cope with future climatic changes to ensure food security (Demirel et al 2020;Mushtaq et al 2022;Gökçe et al 2022).…”
Section: How Does Climate Change Give Rise To Temperature Stress?mentioning
confidence: 99%